2012
DOI: 10.1021/es301381n
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Reactive Thiol Concentrations in Dissolved Organic Matter and Bacterial Cell Membranes in Aquatic Systems

Abstract: Organic thiols are highly reactive ligands and play an important role in the speciation of several metals and organic pollutants in the environment. Although small thiols can be isolated and their concentrations can be estimated using chromatographic and derivatization techniques, estimating concentrations of thiols associated with biomacromolecules and humic substances has been difficult. Here we present a fluorescence-spectroscopy-based method for estimating thiol concentrations in biomacromolecules and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 39 publications
2
66
0
Order By: Relevance
“…Organic thiol functional groups are important DOM complexing ligands for soft Lewis acids, such as Cd and Pb. Their presence influences metal speciation and solubility in natural waters (Joe-Wong et al, 2012). Thiols affinity for metals like Cd and Pb would result in the higher measured binding capacity values observed in the measured complexation constants for natural waters (see Table 1).…”
Section: Complexation Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic thiol functional groups are important DOM complexing ligands for soft Lewis acids, such as Cd and Pb. Their presence influences metal speciation and solubility in natural waters (Joe-Wong et al, 2012). Thiols affinity for metals like Cd and Pb would result in the higher measured binding capacity values observed in the measured complexation constants for natural waters (see Table 1).…”
Section: Complexation Analysesmentioning
confidence: 99%
“…One such functional group not taken into account by the MINTEQ model is the thiol group. These organic sulfide groups (R-SH) are ubiquitous in wetlands (Zhang and Wang, 2004) and are produced by plants mediating interactions with metals (Joe-Wong et al, 2012). Organic thiol functional groups are important DOM complexing ligands for soft Lewis acids, such as Cd and Pb.…”
Section: Complexation Analysesmentioning
confidence: 99%
“…Moreover, the reactivity of dissolved and particulate Hg sulfides with thiols correlated with differences in net methylation potential by methylating microorganisms (Zhang et al, 2012). Likewise, a number of recent studies point to thiols as the site for mercury binding to the cell envelope of methylating bacteria ( Joe-Wong et al, 2012;Hu et al, 2013;Dunham-Cheatham et al, 2014, 2015. While the interactions between Hg and thiols in these studies and the mechanism of Hg uptake by the cell remain unknown, we hypothesize that a simple thiolbased selective extraction could be used to approximate the bioavailable fraction of Hg in anaerobic settings.…”
Section: Introductionmentioning
confidence: 96%
“…Heavy metals, such as Hg, adsorb to proton-active functional groups on bacterial cell envelopes (e.g., Beveridge and Murray, 1976;Fortin and Beveridge, 1997;Daughney et al, 2002;Fein, 2006;Kenney and Fein, 2011), affecting the speciation and distribution of these metals in environmental systems. Recent studies (e.g., GuinĂ© et al, 2006;Mishra et al 2007;2009;2010;Joe-Wong et al, 2012;Pokrovsky et al, 2012;Song et al, 2012;Colombo et al, 2013;Yu et al, 2014) have shown that at least some bacterial cell envelopes contain protonactive sulfhydryl functional groups. Because Hg binds readily and strongly to sulfur compounds (Compeau and Bartha, 1987;Winfrey and Rudd, 1990;Benoit et al, 1999), bacterial adsorption of Hg may dramatically affect the distribution, transport and fate of Hg in geologic systems.…”
Section: Introductionmentioning
confidence: 99%